The Use of the Difference Table to Help Deaf Students Write Bahasa Melayu Essays on Interesting Places to Visit - Rashid, Nurul Addina binti (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
essay writing contributes to 50% of the marks in Bahasa Melayu Penulisan examination. Consequently, the students are at risk of losing a significant portion of the marks if they are not able to write the essays. The difficulties of deaf students to write Bahasa Melayu essays on Interesting Places to Visit are issues of interest in this study. This research involves four students studying in year six at a Special Education School in Seremban, Malaysia. The subjects are expected to adhere to specific criterias in writing an essay on visiting Kuala Lumpur which has been taught in the previous lesson. This research examines the effectiveness of the difference table technique in assisting deaf students to write Bahasa Melayu essays on interesting places to visit. This technique is found to have enhanced the writing skills of the students to write essays of the same theme with different places. The improvement in scores and the skill level achieved by each student proves the effectiveness of this technique.